Respon Pemberian Pupuk Kandang Kambing dan Arang Sekam Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) Varietas Tajuk - Fery Firmansyah; Indriati Husain; Fauzan Zakaria (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Shallots (Allium ascalonicumK.) are vegetable commodities that hold significant importance for society, both in terms of their high economic value and nutritional content. This research aimed to determine the appropriate combination of goat manure and rice husk charcoal doses for the growth and yield of shallot plants. The study was conducted in Bunggalo Village, Telaga Jaya Subdistrict, Gorontalo Regency, from July to September 2024. The research employed a Completely Randomized Design (CRD) with 4 treatmens, each repeated 4 times, resulting in 16 experimental plots. Each plot contained 3 plants, resulting in total of 48 plants. P0 consisted of soil only, P1 consisted of soil, goat manure, and rice husk charcoral in a ratio of (1:2:3), P2 consisted of soil, goat manure and rice husk charcoral in a ratio of (2:1:1) and P3 consisted of soil, goat manure and rice husk charcoral in a ratio of (3:2:1). Each pot contained a total of 6kg of planting media. The observational data ware analyzed using F-test (ANOVA) at a 5% significance level. If significant effect were observed, further analysis was conducted using DMRT at a 5% level. The result indicated that P3 was the best treatment with a (3:2:1) combination for plant height and the nuraber of leaves, while P2 was the best treatment with a (2:1:1) combination for the number of bulbs, fresh weight, and dry weight of shallot plants.